P6.11 THE FRAMINGHAM RISK SCORE IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Nichola Gale*; Margaret Munnery; Ali Albaratti; Dennis Shale; John Cockcroft (Artery Research, 2015)
Background: Patients with chronic obstructive pulmonary disease (COPD) have increased risk of cardiovascular (CV) events and mortality beyond that attributable to smoking. Increased arterial stiffness has been identified in COPD, however it prognostic value has not been established. The Framingham risk score provides a validated estimate of an individual’s future CV risk. We hypothesised that patients with COPD would have greater Framingham risk score and aPWV than controls and that aPWV would relate to the Framingham risk score. Methods: At baseline 524 patients with COPD and 143 controls (free from lung disease) were assessed for; lung function (forced expiratory volume (FEV1), forced vital capacity (FVC) and their ratio), BMI, blood pressure (BP) and aPWV. In addition, medical and smoking history were recorded and used to calculate the Framingham risk score and vascular age. Results: Patients and controls were similar in age, gender and BMI, but patients had greater aPWV, Framingham risk score and vascular age which remained after adjustment for age, and MAP. In COPD, Framingham risk related to age r=0.295, aPWV r= 0.234, SBP r=0.194 and FEV1% predicted r=0.112, (all p<0.01). In controls, Framingham risk score related only to age r=0.383, aPWV r=0.189 and systolic BP r=0.195 p<0.05. Conclusions: The association between the Framingham risk score and aPWV suggests that either may be useful to identify individuals with COPD at risk of future CV events. Further follow-up of this cohort will evaluate the prognostic utility of these measures of CV risk.